2015
DOI: 10.1080/02626667.2014.1000916
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of urban area expansion on groundwater recharge and surface runoff

Abstract: In this surface water modeling study, a new spatial evaluation for assessing the impact of urbanization was applied for the semi-arid watersheds intersecting with the Gaza coastal aquifer. The SWAT model was calibrated and validated in a semi-automated approach for stream flow in the main watersheds. The results show that the model could simulate water budget components adequately within the complex semi-arid watersheds.Linear relationships between the change in urban area and the corresponding change in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
2
41
0
1
Order By: Relevance
“…Statistical analysis shows, with high confidence, that annual precipitation and recharge are normally distributed (i.e., the null hypothesis could not be rejected). Run-off was rather constant and small in all scenarios, comparable to measurements and run-off estimates for loessial sediments (Yair, 1990;Givati and Atzmon, 2009;Eshtawi et al, 2015). The soil water content showed pronounced annual fluctuations, which were superimposed on smooth, multiannual cycles.…”
Section: Water Balancementioning
confidence: 51%
See 2 more Smart Citations
“…Statistical analysis shows, with high confidence, that annual precipitation and recharge are normally distributed (i.e., the null hypothesis could not be rejected). Run-off was rather constant and small in all scenarios, comparable to measurements and run-off estimates for loessial sediments (Yair, 1990;Givati and Atzmon, 2009;Eshtawi et al, 2015). The soil water content showed pronounced annual fluctuations, which were superimposed on smooth, multiannual cycles.…”
Section: Water Balancementioning
confidence: 51%
“…The observed run-off from sandy loess soils in the region is very small (Yair, 1990;Givati and Atzmon, 2009;Eshtawi et al, 2015). For the entire catchment of the ephemeral Besor River, which is covered in large parts by sandy loess sediments, the run-off coefficient for 1985/6-2009/10, defined as % of annual precipitation, was only 1.3% (Givati and Atzmon, 2009).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, EIA is of critical importance in how urban areas translate rainfall to runoff, where high percentages of EIA contribute to rapid proliferation of stormwater runoff into adjacent channels, resulting in an elevated flood risk to urban areas (Miller et al 2014). In the same study that assessed threshold impacts on infiltration, Eshtawi et al (2014) identified that a 1% increase in urban area yielded up to a 100% increase in runoff. Whilst the impact of impervious surfaces on runoff is relatively well understood, there remains a degree of uncertainty about the role of pervious areas within the urban environment.…”
Section: Surface Runoff Dynamicsmentioning
confidence: 99%
“…The previous studies estimated the range of rainfall recharge between 25 and 48 hm 3 /year, depending on the methodology used and the base year or period. The authors of this paper (Eshtawi et al 2015) performed a surface water modeling with surface water model (SWAT) to quantify the impact of urban area expansion on groundwater recharge and surface runoff. They developed a spatial distribution of percolation within the Gaza aquifer domain from 2004 to 2010.…”
Section: Introductionmentioning
confidence: 99%